The Influence of Guided Inquiry Learning Models on Students Creative Thinking Abilities on Reaction Rate Material - Hutami, Sulia; Burhanuddin, Burhanuddin; Ariani, Sunniarti; Al Idrus, Syarifah Wahidah (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
This research examines the effect of the guided inquiry learning model on students' creative thinking abilities, focusing on studying chemical reaction rate material in Class XI Science at SMAN 4 Praya. This research adopts a quantitative research design with a quasi-experimental research type. The population in this study were all class XI MIPA students at SMAN 4 Praya, consisting of 237 people spread across 7 classes. The sampling technique uses non-probability sampling, seeing a similarity in students' average daily test scores with students in classes XI IPA 3 as the control class and XI IPA 6 as the experimental class. The experimental group was given a guided inquiry learning model, while the control group used conventional teaching methods. This research assesses creative thinking abilities through a description test including three indicators: originality, fluency, and flexibility. In this research, the data analysis technique uses a series of statistical tests, including the Kolmogorov-Smirnov normality and homogeneity tests. Hypothesis testing uses the independent sample t-test. The hypothesis test showed that the t-test results prove that tcount ≥ ttable , namely 4.31 ≥ 2.03, and a significant value of 0.00 ˃ 0.05, then H0 is rejected, and H1 is accepted. Thus, it can be concluded that the guided inquiry learning model positively affects students' creative thinking abilities in the reaction rate material for class XI Science at SMAN 4 Praya. This can also be seen from the results that the average value of the experimental group is higher than the control group's, with the experimental class's average value being 79.03% and the average value of the control class being 62.42%.